Two new species and one new synonymy of the pygmy grasshopper genus Formosatettix Tinkham, (Orthoptera: Tetrigidae) from China. (3rd July 2021) - Ding, Jian-Hua; Pan, Zhi-Xiang; Zha, Ling-Sheng
ABSTRACT: Formosatettix nanjiensis : Zha & Ding sp. nov . and F. taibaiensis Zha & Ding sp. nov . are described from Zhejiang and Shaanxi provinces of China, respectively. New synonymy is established: Formosatettix tianmushanensis Zheng & Li, 2001 =  Formosatettix zhejiangensis Deng, 2019 syn. nov . An updated species key to the genus Formosatettix Tinkham, 1937 is provided.http://www.zoobank.org/urn:lsid:zoobank.org:pub:E9BF3BCF-D8B3-4A10-8EE7-365EA28A2D6F